2019
DOI: 10.1103/physrevb.100.121104
|View full text |Cite
|
Sign up to set email alerts
|

Surface states and Rashba-type spin polarization in antiferromagnetic MnBi2Te4 (0001)

Abstract: The layered van der Waals antiferromagnet MnBi2Te4 has been predicted to combine the band ordering of archetypical topological insulators like Bi2Te3 with the magnetism of Mn, making this material a viable candidate for the realization of various magnetic topological states. We have systematically investigated the surface electronic structure of MnBi2Te4(0001) single crystals by use of spin-and angle-resolved photoelectron spectroscopy (ARPES) experiments. In line with theoretical predictions, the results reve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
86
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(97 citation statements)
references
References 49 publications
(99 reference statements)
9
86
0
Order By: Relevance
“…Two branches of the dispersion intersect each other at a single Dirac point, showing the gapless nature of the TSS. This is in sharp contrast to the earlier reports of a magnetic order induced surface gap in the order of hundred-meVs in both MnBi2Te4 [2,4,9,17] and MnBi4Te7 [14,15]. On the contrary, our results are consistent with the recent observation of a gapless TSS in MnBi2Te4 [32][33][34][35].…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Two branches of the dispersion intersect each other at a single Dirac point, showing the gapless nature of the TSS. This is in sharp contrast to the earlier reports of a magnetic order induced surface gap in the order of hundred-meVs in both MnBi2Te4 [2,4,9,17] and MnBi4Te7 [14,15]. On the contrary, our results are consistent with the recent observation of a gapless TSS in MnBi2Te4 [32][33][34][35].…”
supporting
confidence: 76%
“…A universal gapless Dirac cone is observed at the MnBi2Te4 terminated (0001) surfaces in all systems. This is in sharp contrast to the expected gap from the original antiferromagnetic ground state [2][3][4]9,[17][18][19], indicating an altered magnetic structure near the surface, possibly due to the surface termination. In the meantime, the electron band dispersion of the surface states, presumably dominated by the top surface [20,21], is found to be sensitive to different stackings of the underlying MnBi2Te4 and Bi2Te3 layers.…”
mentioning
confidence: 66%
“…Subsequently, single crystals of MnBi 2n Te 3n+1 were grown and physical properties, including electrical and thermal transport, magnetization, neutron scattering, etc., were measured which support possible realization of the axion insulator in these materials [16][17][18][19][20][21]. While some ARPES studies reported observation of a gapped surface state in MnBi 2n Te 3n+1 and thus possible axion insulator behavior [22][23][24][25], many others showed evidence that the surface state in this material remains gapless or diminished gap down to low temperatures [26][27][28][29][30]. The latter may be a result of weak hybridization between the magnetic states and the topological electronic states [30] or possibly a different (or disordered) magnetic structure at the top Mn-Te layer [26,28].…”
Section: Introductionmentioning
confidence: 73%
“…Recently, MnBi 2 Te 4 , a van der Waals (vdW) compound composed of the septuple layers (SLs) of [MnBi 2 Te 4 ], was identified as an intrinsic magnetic topological material with clean band structure ( 10 32 ). Unfortunately, magnetic moments in MnBi 2 Te 4 are antiferromagnetically (AFM) coupled across adjacent [MnBi 2 Te 4 ] planes ( 15 , 31 ).…”
Section: Introductionmentioning
confidence: 99%